O ENADE como instrumento sinalizador para avaliação e qualificação de cursos de graduação em turismo - Marcelino, Thays de Oliveira (My University, 2017)
The present study tackles the issue of performance in the national exam ENADE with special regard to scientific and pedagogical evaluation of undergraduate Leisure and Tourism courses. In other words, this study aims to identify and analyse changing processes in the pedagogical project as well as in evaluating practices resulting from an analytical-interpretative process of the referred exam and its ensuing report, conducted by the course supervisors. Methodologically, this exploratory and qualitative research is based on a interview-oriented survey, which centres itself around four axes: organisation of the operational process of analysis, concepts of tourism liable to proof, evaluation of the questions and methodological and pedagogical concepts. In terms of guidance, as the 2015 report had not yet been made available at the time of this investigation, the 2012 edition of the exam was selected along with Rio Grande do Sul-based undergraduate Leisure and Tourism courses which had participated in three previous editions of the aforementioned exam. Taking into consideration the established criteria, four course coordinators from different institutions were interviewed. Considering the interviewees' words, an in-depth look into the exam is a regular practice in all analysed courses. However, some stand out as far as how they vary in terms of perception and management. Some instances which illustrate the discussion are: analyses of error/mistake frequency and competences needed to solve them, especially when the pedagogical project of the course is taken into account; prevalence of actions concerning the update of specific contents; the use of ENADE-like questions in regular exams; offer of mock tests; an urge to encourage professors to take up a more critical approach. As far as Tourism scientific theories are concerned, there are mentions of implicit aspects of theories even if they are not made explicit as in consumption potential in market segmentation, competitivity, infrastructure and superstructure elements, and sustainable tourim planning. Similarly, from a pedagogical standpoint, some positive elements are highlighted in a positive light such as questions which centre themselves around contextualised situations and incentive to ensure critical thinking, without having to resort to explicitation and detailment of theoretical bases and everyday practices. Once the data is analysed by the researcher, the potentiality of the contribution is highlighted as a tool not only for evaluative purposes, but also complementary to identification and comprehension of cognitive and metacognitive operations which are relevant in the development of a tourismologist.
O presente estudo tem como objeto o aproveitamento da prova do Enade para qualificação científica e pedagógica de cursos de graduação em Turismo. Em outras palavras, busca identificar e analisar processos de mudança nos projetos pedagógicos e nas respectivas práticas pedagógicas e avaliativas decorrentes do processo analítico-interpretativo da prova e do correspondente relatório, conduzido pelas coordenações de curso. Metodologicamente, a pesquisa, de natureza qualitativa e exploratória, utiliza como técnica para a coleta de informações a entrevista semiestruturada, a qual girou em torno de quatro eixos: organização do processo operacional de análise, concepções de turismo subjacentes às questões, avaliação das questões de cunho geral e concepções pedagógicas e metodológicas igualmente subjacentes às questões. Operacionalmente definiu-se como recorte temporal e espacial, respectivamente, a prova de 2012 (não havia sido disponibilizado o relatório de 2015 quando se desenvolveu a investigação) e cursos de graduação em Turismo do Rio Grande do Sul que haviam participado do exame em suas três edições e cuja coordenação se disponibilizou a participar. Face aos critérios estabelecidos, entrevistaram-se coordenadores de quatro instituições, sendo elas de caráter público estatal, público comunitário e confessional. Na voz dos sujeitos entrevistados, a explicação aos alunos da natureza e importância da prova é uma ação comum a todos os cursos. Outras, porém se destacam com variações de percepções e formas de condução. Tem-se como exemplos, entre outros: análise do tipo da incidência de erros e das correspondentes competências requeridas para saná-los, confrontados com o projeto pedagógico do curso; prevalência de ações relativas à atualização de conteúdos pontuais; inserção, em avaliações, de questões modelo Enade; realização de simulados; solicitação aos professores de abordagem mais reflexiva dos conteúdos. No que tange à percepção de teorias científicas sobre o turismo subjacentes às questões, tende haver menção a aspectos implícitos nas teorias, sem que estas sejam explicitadas, tais como potencial de consumo nos segmentos de mercado, competitividade, elementos de infraestrutura e superestrutura, planejamento de turismo sustentável. De modo igual, do ponto de vista pedagógico, são pontuados positivamente elementos como questões sobre situações contextualizadas, exigência de posicionamento crítico, sem explicitação e detalhamento das respectivas bases teóricas e práticas cotidianas decorrentes. Analisada a prova pela pesquisadora, identificou-se a potencialidade de sua contribuição como instrumento avaliativo complementar para identificação e compreensão e desenvolvimento de operações cognitivas e metacognitivas relevantes ao processo de formação do turismólogo.
Keywords: Turismo - Estudo e ensino (Superior); Ensino superior - Brasil; Tourism - Study and teaching (Higher); Education, Higher - Brazil